1997
DOI: 10.1039/a606734d
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of current-doubling reactions at ZnO photoanodes

Abstract: The mechanism of photocurrent-doubling reactions at ZnO single-crystal electrodes in aqueous formate, tartrate and methanol solutions has been reinvestigated. On the basis of steady-state photocurrent measurements in a wide range of light intensity it is concluded that, in the case of formate and tartrate, the electron-injecting species arises from a reaction between the currentdoubling agent and oxygen, formed in the photoanodic decomposition of ZnO. This is not the case for methanol. These conclusions are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
6
18
0
Order By: Relevance
“… 11 , 23 , 31 This photocurrent doubling mechanism (where one photon generates two conduction band electrons) has been observed previously under low light intensity conditions on TiO 2 and ZnO. 11 , 32 , 33 However, we note that Schoenmakers et al 33 have reported a reduction in the quantum efficiency of methanol oxidation on ZnO from 2 to 1 when increasing the light intensity from ∼0.005 to 5 suns. The results we report here provide an explanation for Schoenmakers et al’s observation and indicate that under ∼1 sun irradiation conditions, where there is significant hole accumulation at the oxide surface, both steps of methanol oxidation are driven by photogenerated valence band holes.…”
Section: Discussionsupporting
confidence: 75%
“… 11 , 23 , 31 This photocurrent doubling mechanism (where one photon generates two conduction band electrons) has been observed previously under low light intensity conditions on TiO 2 and ZnO. 11 , 32 , 33 However, we note that Schoenmakers et al 33 have reported a reduction in the quantum efficiency of methanol oxidation on ZnO from 2 to 1 when increasing the light intensity from ∼0.005 to 5 suns. The results we report here provide an explanation for Schoenmakers et al’s observation and indicate that under ∼1 sun irradiation conditions, where there is significant hole accumulation at the oxide surface, both steps of methanol oxidation are driven by photogenerated valence band holes.…”
Section: Discussionsupporting
confidence: 75%
“…They considered the most probable explanation was that alcohol adsorbs at the TiO 2 surface and blocks the sites that would otherwise act as recombination. A similar proposal was made by Schoenmakers, Vanmaekelbergh and Kelly [42] for the oxidation of methanol on single-crystal ZnO. In a study of photoelectrochemical oxidation of methanol in Na 2 SO 4 solution John and co-workers [43] conclude that the limiting step was interfacial charge transfer and that the concentration of hydroxyl ions (the precursors of hydroxyl radicals) did not influence photocurrents at pH 9.…”
Section: Small Electrodessupporting
confidence: 57%
“…With pure ZnO as a top layer, it is furthermore assured that the conduction band edge is located energetically higher than the reduction level [43]. However, ZnO dissolves in most electrolytes making an anticorrosion layer indispensable [44]. Among other oxides, TiO 2 is known to be chemically stable, making it a potential candidate for a thin photoanode overlayer preventing corrosion of the underlying…”
Section: Oxides As Pec Electrodesmentioning
confidence: 99%